The Belt and Road Initiative and its impact on Latin America’s connectivity: a case study of Chile and Peru - Germanò, Marco André (Seminário Pesquisar China Contemporânea, 2021)
Since its launch in 2013, the Belt and Route Initiative (BRI) - in Chinese Yi Dai Yi Lou  (????) - has attracted the attention of observers from around the world for its goals and the magnitude of its investments. In academic circles, several debates emerged regarding the economic, political, and geostrategic aspects of the initiative. Some studies highlight the BRI's ability to promote a new global financial architecture, others its geopolitical impacts. Although these works are extremely timely, the contributions that investigate how the BRI concretely produces greater regional and global connectivity, especially in Latin America and the Caribbean (LAC), are incipient. The concept of connectivity is central to the initiative, appearing in several speeches and official documents (CHINA, 2015a; JINPING, 2017; CGTN, 2020). In the words of the National Development and Reform Commission (NDRC), the BRI is an initiative that mainly seeks to strengthen the “physical, institutional, and cultural connectivity between all the countries that are part of it” (CHINA, 2015b). As the BRI consolidates in LAC, connectivity expands through investments in large infrastructure projects that drive new and greater trade flows. In addition to heavy engineering and increased commercial transactions, the BRI also fosters the construction of a complementary legal infrastructure that regulates economic interactions, safeguarding the interests of investors and host countries (LIAO, 2019). Legal connectivity encompasses, e.g., Free Trade Agreements (FTAs), cross-border regulations, customs and financial cooperation mechanisms. (...)